2009
DOI: 10.1134/s0006297909020163
|View full text |Cite
|
Sign up to set email alerts
|

Protein aggregation and neurodegeneration: Clues from a yeast model of Huntington’s disease

Abstract: A number of neurodegenerative diseases are accompanied by the appearance of intracellular protein aggregates. Huntington's disease (HD) is caused by a mutation in a gene encoding huntingtin. The mutation causes the expansion of the polyglutamine (polyQ) domain and consequently polyQ-containing aggregates accumulate and neurons in the striatum die. The role of the aggregates is still not clear: they may be the cause of cytotoxicity or a manifestation of the cellular attempt to remove the misfolded proteins. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…PolyQ expression (103Q but not 103QP) also induced ER stress leading to UPR (Duennwald and Lindquist, 2008), and has also been proposed to lead to lethal impairment of cell cycle progression (Bocharova et al, 2008, 2009). ER and cell cycle impairments are believed to be consequences of the impairment of specific branches of the UPS pathway by polyQ expression (103Q), including the ERAD and anaphase promoting complex (APC) pathways (Bocharova et al, 2008, 2009; Duennwald and Lindquist, 2008). The mitochondrion-associated protein degradation pathway (MAD) shares pivotal components with the ERAD pathway (Heo et al, 2010; Taylor and Rutter, 2011).…”
Section: Yeast Models Expressing Neurotoxic Proteinsmentioning
confidence: 99%
“…PolyQ expression (103Q but not 103QP) also induced ER stress leading to UPR (Duennwald and Lindquist, 2008), and has also been proposed to lead to lethal impairment of cell cycle progression (Bocharova et al, 2008, 2009). ER and cell cycle impairments are believed to be consequences of the impairment of specific branches of the UPS pathway by polyQ expression (103Q), including the ERAD and anaphase promoting complex (APC) pathways (Bocharova et al, 2008, 2009; Duennwald and Lindquist, 2008). The mitochondrion-associated protein degradation pathway (MAD) shares pivotal components with the ERAD pathway (Heo et al, 2010; Taylor and Rutter, 2011).…”
Section: Yeast Models Expressing Neurotoxic Proteinsmentioning
confidence: 99%
“…HD inheritance is autosomal dominant and consequently the prevailing view is that mHtt mediated symptoms result from a toxic gain-offunction mechanism although loss-of-function mechanisms for mHtt and Htt are also proposed [8,9]. Htt is conserved among vertebrates [10], is localized mainly in cytoplasm and exhibits anti-apopptotic properties [11,12]. Importantly, Htt expression in different tissues does not correspond with the restricted distribution of neuropathologic changes in HD [13] but the protein has been shown to be required for mammalian neurogenesis [14].…”
Section: Huntington's Diseasementioning
confidence: 99%
“…In normal neurons, the late form of anaphase promoting complex (APC/C-Cdh1) constantly degrades PFKFB3, thereby suppressing the rate of glycolysis. [24,25] Alterations in the efficiency of different metabolic pathways can be due to damaged chaperonins that have been blocked by misfolded and aggregated protein forms. [23] A similar effect has also been observed upon artificial inhibition of this ubiquitinase, leading to a shift from respiration to glycolysis and the consequent oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] There is evidence that, in neurons affected by Alzheimer's, Parkinson's or Huntington's disease, the protein degradation machinery is overloaded by protein aggregates. [24,25] Alterations in the efficiency of different metabolic pathways can be due to damaged chaperonins that have been blocked by misfolded and aggregated protein forms. [26,27] Although the level of PFKFB3 has not been measured in affected neurons, it has recently been shown that APC/C-Cdh1 activity is inhibited during neuronal death induced by glutamate excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%